The influence of Teamwork, Communication, and Work Environment on Teacher Performance at SDN Kutabaru 1 Tangerang Regency - Utami, Atrisia Aulia; Masruri, Masruri; Trianto , Eko (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze and determine the effect of independent variables on the dependent variable partially and simultaneously at SDN Kutabaru 1 Tangerang Regency. The method used is quantitative method, with data collection methods using literature studies, questionnaires (questionnaires), and observation (observation) conducted in February-May 2024. The sampling technique used was a saturated sample using the calculation of the SPSS version 25 application program. The population of this study were teachers at SDN Kutabaru 1 Tangerang Regency. The sample contained in this study were 30 respondents. The results of this study indicate that all question items are valid and reliable. This can be proven by the Teamwork variable by the tcount value of 2.915> from the ttable value of 1.705 with a sig value of 0.007 < 0.05. Which means it shows that teamwork has a positive and significant effect on teacher performance. Communication variable by sig value 0.000 < 0.05. And the tcount value is 4.060> from the ttable value of 1.705. Which means it shows that the value of communication has a positive and significant effect on teacher performance. The work environment variable by the tcount value of 2.984> from the ttable value of 1.705 and a significant value of 0.006 <0.05. Which means it shows that the work environment has a positive and significant effect on teacher performance. Based on the results of this study, it has a positive and significant effect together (simultaneously) the Fcount value is 12.494> 2.98. So it can be concluded that H0 is rejected and Ha is accepted, which means that the Teamwork, Communication, and Work Environment variables simultaneously affect the teacher performance variable.